2017
DOI: 10.1007/s13300-017-0245-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Adding Alogliptin to Metformin Plus Sulfonylurea with Other DPP-4 Inhibitors in Type 2 Diabetes: A Systematic Review and Network Meta-Analysis

Abstract: IntroductionAlogliptin is an oral antihyperglycemic agent that is a selective inhibitor of the enzyme dipeptidyl peptidase-4 (DPP-4), approved for the treatment of type 2 diabetes mellitus (T2DM). There currently exists no comparative data to support the use of alogliptin in combination with metformin (met) and sulfonylurea (SU). A decision-focused network meta-analysis (NMA) was performed to compare the relative efficacy and safety of alogliptin 25 mg once daily to other DPP-4 inhibitors as part of a triple t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Notably, SGLT-2i yielded significant improvements in this parameter when compared with all other agents except GLP-1RA and AGI and was therefore ranked the best. A previous NMA by Kay et al [ 57 ] demonstrated that all DPP-4is were associated with mean body weight gains relative to placebo when added to metformin and SU. Although that study focused on triple combination therapy (DPP-4i + Met + SU), these findings were consistent with our study results.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, SGLT-2i yielded significant improvements in this parameter when compared with all other agents except GLP-1RA and AGI and was therefore ranked the best. A previous NMA by Kay et al [ 57 ] demonstrated that all DPP-4is were associated with mean body weight gains relative to placebo when added to metformin and SU. Although that study focused on triple combination therapy (DPP-4i + Met + SU), these findings were consistent with our study results.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are further supported by a meta-analysis examining the efficacy and safety of alogliptin as monotherapy or combination therapy [78, 79]. Here, the number of patients who discontinued due to AEs was not significantly different in patients treated with alogliptin versus placebo or other antidiabetic control treatments (odds ratio [OR] 0.83; 95% confidence interval [CI] 0.61–1.58 for alogliptin 12.5 mg; OR 0.98; 95% CI 0.44–1.58 for alogliptin 25 mg) [78].…”
Section: Benefit Evaluationmentioning
confidence: 65%
“…Meta-analyses have not found any significant difference in hypoglycemic action among different DPP-4 inhibitors [36, 37]. In a meta-analysis focusing on alogliptin, Kay et al compared the effects of alogliptin with those of four other DPP-4 inhibitors (linagliptin, saxagliptin, sitagliptin, and vildagliptin) in patients with insufficient blood glucose control by treatment with metformin and sulfonylurea (SU), reporting that alogliptin did not differ from the other DPP-4 inhibitors in terms of efficacy and safety [38]. The excretory pathway differs among DPP-4 inhibitors.…”
Section: Discussionmentioning
confidence: 99%